OClO and BrO observations in the volcanic plume of Mt. Etna: implications on the chemistry of chlorine and bromine species in volcanic plumes - Gliß, Jonas; Bobrowski, Nicole; Vogel, Leif; Pöhler, Denis; Platt, Ulrich (Atmospheric chemistry and physics, 2015)
Spatial and temporal profiles of chlorine dioxide (OClO), bromine monoxide (BrO) and sulfur dioxide (SO2) of the volcanic plume at Mt. Etna, Italy, were investigated in September 2012 using Multi-Axis Differential Optical Absorption Spectroscopy (MAX-DOAS). OClO was detected in 119 individual measurements covering plume ages up to 6 min. BrO could be detected in 452 spectra up to 23 min downwind. The retrieved slant column densities (SCDs) reached maximum values of 2.0 × 1014 molecules cm-2 (OClO) and 1.1 × 1015 molecules cm-2 (BrO). Mean mixing ratios of BrO and OClO were estimated assuming a circular plume cross section. Furthermore, ClO mixing ratios were derived directly from the BrO and OClO-SCDs. Average abundances of BrO = 1.35 ppb, OClO = 300 ppt and ClO = 139 ppt were found in the young plume (plume age τ < 4 min) with peak values of 2.7 ppb (BrO), 600 ppt (OClO) and 235 ppt (ClO) respectively. The chemical evolution of BrO and OClO in the plume was investigated in great detail by analysing the OClO/SO2 and BrO/SO2 ratios as a function of plume age τ. A marked increase of both ratios was observed in the young plume (τ < 142 s) and a levelling off at larger plume ages showing mean SO2 ratios of 3.17 × 10-5 (OClO/SO2) and 1.65 × 10-4 (BrO/SO2). OClO was less abundant in the plume compared to BrO with a mean OClO/BrO ratio of 0.16 at plume ages exceeding 3 min. A measurement performed in the early morning at low solar radiances revealed BrO/SO2 and OClO/SO2 ratios increasing with time. This observation substantiates the importance of photochemistry regarding the formation of BrO and OClO in volcanic plumes. These findings support the current understanding of the underlying chemistry, namely, that BrO is formed in an autocatalytic, heterogeneous reaction mechanism (in literature often referred to as "bromine explosio") and that OClO is formed in the reaction of OClO with BrO. These new findings, especially the very detailed observation of the BrO and OClO formation in the young plume, were used to infer the prevailing Cl-atom concentrations in the plume. Relatively small values ranging from [Cl] = 2.5 × 106 cm-3 (assuming 80 ppb background O3) to [Cl] = 2.0 × 108 cm-3 (at 1 ppb O3) were calculated at plume ages of about 2 min. Based on these Cl abundances, a potential – chlorine-induced – depletion of tropospheric methane (CH4) in the plume was investigated. CH4 lifetimes between 14 h (at 1 ppb O3) and 47 days (at 80 ppb O3) were derived. While these lifetimes are considerably shorter than the atmospheric lifetime of CH4, the impact of gaseous chlorine on the CH4 budget in the plume environment should nevertheless be relatively small due to plume dispersion (decreasing Cl concentrations) and ongoing mixing of the plume with the surrounding atmosphere (replenishing O3 and CH4). In addition, all spectra were analysed for signatures of IO, OIO and BrO. None of these species could be detected. Upper limits for IO/SO2, OIO/SO2 and OBrO/SO2 are 1.8 × 10-6, 2.0 × 10-5 and 1.1 × 10-5 respectively.